Effective optical parameters of thin-film and bulk metamaterials of metallodielectric nanosandwiches - C. Tserkezis; N. Stefanou; N. Papanikolaou (Optics Communications, 2010)
We report on the effective optical response of single- and multilayer periodic structures of metallodielectric nanosandwiches on the basis of rigorous, full-electrodynamic calculations by the extended layer-multiple-scattering method. It is shown that the complex photonic band structure and the reflection coefficient of the infinite and semi-infinite crystal, respectively, provide reliable bulk effective parameters, which can be used as a reference in order to resolve ambiguities and problems in the determination of these parameters for finite slabs by the S-matrix retrieval procedure. Our results show that the structures under consideration exhibit strong artificial optical magnetism and thin films consisting of a few layers already behave like the bulk metamaterial.